DIAKONIA TO INCREASE THE INVOLVEMENT OF CATHOLIC YOUTH AT SAINT ANDREW KEMPAWA STATION - Silvyana Sembiring; Paulinus Tibo (UIN Sunan Kalijaga Yogyakarta, 2026)
This study is motivated by the important role of Catholic Youth (Orang Muda Katolik/OMK) in the life of the Church. However, their involvement still faces various challenges that affect their active participation in Church ministries. This study aims to describe the diaconal ministry of Catholic Youth and their involvement in the life of the Church at St. Andreas Kempawa Station. This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. Theoretically, this study is based on the concept of diakonia, which includes charitable service, empowerment service, and social transformation, as well as the concept of Catholic Youth involvement in ecclesial life. The results show that the diaconal ministry of Catholic Youth at St. Andreas Kempawa Station is manifested through charitable service, empowerment service, and social transformation. Meanwhile, the involvement of Catholic Youth is reflected in their active participation in liturgy, fellowship (koinonia), and charitable service (diakonia). These various forms of involvement contribute to strengthening faith, character formation, and enhancing the sense of responsibility and solidarity among Catholic Youth in the life of the Church and society. Keyword: diakonia, involvement, Catholic Youth, pastoral ministry, Catholic Church. Penelitian ini dilatarbelakangi oleh pentingnya peran Orang Muda Katolik (OMK) dalam kehidupan menggereja, namun keterlibatan mereka masih menghadapi berbagai tantangan yang memengaruhi partisipasi aktif dalam pelayanan Gereja. Penelitian ini bertujuan untuk mendeskripsikan diakonia Orang Muda Katolik dan keterlibatan Orang Muda Katolik di Stasi Santo Andreas Kempawa. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Secara teoretis, penelitian ini menggunakan konsep diakonia yang meliputi pelayanan kasih, pelayanan pemberdayaan, dan transformasi sosial, serta konsep keterlibatan Orang Muda Katolik dalam kehidupan menggereja. Hasil penelitian menunjukkan bahwa diakonia Orang Muda Katolik di Stasi Santo Andreas Kempawa diwujudkan melalui pelayanan kasih, pelayanan pemberdayaan, dan transformasi sosial. Sementara itu, keterlibatan Orang Muda Katolik tampak melalui partisipasi aktif dalam bidang liturgi, persekutuan (koinonia), dan pelayanan kasih (diakonia). Berbagai bentuk keterlibatan tersebut berkontribusi terhadap penguatan iman, pembentukan karakter, serta peningkatan rasa tanggung jawab dan solidaritas anggota OMK dalam kehidupan Gereja dan masyarakat. Kata kunci: diakonia, keterlibatan, Orang Muda Katolik, pelayanan pastoral, Gereja Katolik.